Studi Pakan Burung Perkici Pelangi (Trichoglossus haematodus Linnaeus, 1771) dalam Laboratorium Penangkaran - Widodo, W (Universitas Atma Jaya Yogyakarta, 2006)
During the 2002-2003 period, the research was done to study 11 Rainbow Lorikeetsreared in an animal house laboratory. The aim of this research was to find the foodrations formule of the Rainbow Lorikeets so that those birds can be able to grow andbreed well. The food rations were composed of 26.3% local bird foods (521), 35.09%lampung bananas, 8.77% slice corns, 10.5% boiled quails eggs, 1.75% white bread,bean sprouts and red sugar are 8.77%, respectively. All of food materials were mixedon the plastic cup and mixed with 450 ml of water, then pulverized like sweetporridge. That porridge was given to birds in cafeteria and the water was made readyâ€œad libitumâ€ everyday. The results have shown that giving food rations formula canstimulate two pairs of the Rainbow Lorikeets breeding and during the 2002-2003period they produced three young birds.